AKTIVITAS ANTIOKSIDAN DAN KARAKTERISTIK FISIK SUSU KAMBING PASTEURISASI DENGAN PENAMBAHAN BUAH LONTAR (Borassus flabellifer L.) - Rahman, Andi Nabila; Maruddin, Fatma; Said, Irfan; Taufik, Muhammad; Taggo, Syamsuddin (Department of Agroindustrial Technology, Bogor Agricultural University, 2023)
Palmyra fruit (Borassus flabellifer L.) contains active compounds and nutritional content that can maintain and improve the quality of processed goat milk products. The objective of this research was to analyze the antioxidant activity and physical characteristics of goat's milk pasteurized using palmyra fruit. A completely randomized design (CRD) with 5 treatments with 3 replications was used in this research with parameters of antioxidant activity, viscosity and pH. The number of panelists in organoleptic testing was 25 people. Treatments with the addition of palmyra fruit percentage of the total volume of milk made were 0%, 10%, 12%, 14%, and 16% (w/v). The addition of palmyra fruit to pasteurized goat milk had an effect (P<0.01) on antioxidant activity, viscosity, sweetness, milk taste and palmyra taste, however, it had no effect on the pH value. The use of 10% palm fruit in the processing of pasteurized goat milk will produce the best quality based on antioxidant studies and its physical characteristics. Keywords: antioxidants, goat's milk, palmyra fruit, pasteurization, physical properties